KARAKTERISTIK REMAJA PENYALAHGUNA NAPZA YANG MENJALANI REHABILITASI RAWAT JALAN DI KLINIK PRATAMA BNNP RIAU - Refianti, Eka "; Hasanah, Oswati "; ", Misrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Drug abuse is not only done by adults, but also by children and teenagers. The purpose of this research is to describe the characteristics of adolescent drug abusers undergoing Rehabilitation in outpatient Clinic Primary in BNN Riau Province. This research is descriptive with retrospective approach. Samples in this study is 50 respondent take with total sampling technique. Instruments used in this research is check list sheet, data is retrieved based on existing data on Adiction Severity Index (ASI). The result showed that majority respondent is 21 years old (26%), majority is male (62%), majority level of educationis High Scholar (60%), mostly employment status is unemployment (36%), the most widely used drugs is Methamphetamine (64.8%), for 1-3 years(66%), nearly all respondent undergo first rehabilitation (92%), majority live with parents (44%), and do not live with other drug abuser (63.5%), from all the respondent none involved in legal issues (100%). This research recommendation for BNN to provide information of drug abuse side effects to the whole community, especially adolescents in the Riau Province and provide motivation to adolescents so that they do not use drug. Keyword: Adolescent, Characteristics, Drugs, Rehabilitation